Question
upstudy study bank question image url

-The second difference is 10 - The first two terms are equa \( T_{1}=T_{2} \) \( T_{1}+T_{2}+T_{3}=28 \)

Ask by Huang Lawson. in South Africa
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The first three terms are 6, 6, and 16.

Solution

Let's extract the known conditions from the problem: 1. The second difference of a sequence is 10. 2. The first two terms are equal: \( T_1 = T_2 \). 3. The sum of the first three terms is 28: \( T_1 + T_2 + T_3 = 28 \). ### Step 1: Define the terms Since \( T_1 = T_2 \), we can denote both terms as \( T_1 = T_2 = a \). ### Step 2: Express the third term From the sum of the first three terms, we have: \[ T_1 + T_2 + T_3 = a + a + T_3 = 2a + T_3 = 28 \] This simplifies to: \[ T_3 = 28 - 2a \] ### Step 3: Understand the second difference The second difference being 10 implies that the sequence is quadratic. The second difference of a quadratic sequence is constant. Let’s denote the first term as \( T_1 = a \), the second term as \( T_2 = a \), and the third term as \( T_3 = 28 - 2a \). The first differences can be expressed as: - \( D_1 = T_2 - T_1 = a - a = 0 \) - \( D_2 = T_3 - T_2 = (28 - 2a) - a = 28 - 3a \) The second difference is: \[ \Delta D = D_2 - D_1 = (28 - 3a) - 0 = 28 - 3a \] Setting this equal to the known second difference of 10: \[ 28 - 3a = 10 \] ### Step 4: Solve for \( a \) Now, we can solve for \( a \): \[ 28 - 3a = 10 \\ -3a = 10 - 28 \\ -3a = -18 \\ a = 6 \] ### Step 5: Find \( T_3 \) Now that we have \( a \), we can find \( T_3 \): \[ T_3 = 28 - 2a = 28 - 2(6) = 28 - 12 = 16 \] ### Final Terms Thus, the terms are: - \( T_1 = 6 \) - \( T_2 = 6 \) - \( T_3 = 16 \) ### Conclusion The first three terms of the sequence are \( T_1 = 6 \), \( T_2 = 6 \), and \( T_3 = 16 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

In this scenario, you're dealing with a quadratic sequence where the second difference is constant at 10. This indicates that the sequence grows quadratically, meaning that if you were to list the terms of this sequence, their behavior would curve upwards. Such sequences are fascinating because they link closely with parabolic functions, which are omnipresent in real-world applications, like physics in projectile motion! The first two terms being equal simplifies things quite a bit—let's call them both \( a \). Since \( T_{1} = T_{2} = a \), we can express the third term \( T_{3} \) as \( a + d \) (where \( d \) is the difference from \( T_{2} \) to \( T_{3} \)). The equation \( a + a + (a + d) = 28 \) can help you find \( a \) and subsequently \( d \). So dust off those algebra skills and solve for the terms to uncover the secrets of this charming sequence!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy